Atomic‐Thin ZnO Sheet for Visible‐Blind Ultraviolet Photodetection. Issue 47 (2nd November 2020) - Yu, Huihui; Liao, Qingliang; Kang, Zhuo; Wang, Zhenyu; Liu, Baishan; Zhang, Xiankun; Du, Junli; Ou, Yang; Hong, Mengyu; Xiao, Jiankun; Zhang, Zheng; Zhang, Yue
Abstract: The atomic‐thin 2D semiconductors have emerged as plausible candidates for future optoelectronics with higher performance in terms of the scaling process. However, currently reported 2D photodetectors still have huge shortcomings in ultraviolet and especially visible‐blind wavelengths. Here, a simple and nontoxic surfactant‐assisted synthesis strategy is reported for the controllable growth of atomically thin (1.5 to 4 nm) ZnO nanosheets with size ranging from 3 to 30 µm. Benefit from the short carbon chains and the water‐soluble ability of sodium dodecyl sulfate (SDS), the synthesized ZnO nanosheets possess high crystal quality and clean surface, leading to good compatibility with traditional micromanufacturing technology and high sensitivity to UV light. The photodetectors constructed with ZnO demonstrate the highest responsivity (up to 2.0 × 10 4 A W −1 ) and detectivity ( D * = 6.83 × 10 14 Jones) at a visible‐blind wavelength of 254 nm, and the photoresponse speed is optimized by the 400 °C annealing treatment (τR = 3.97 s, τD = 5.32 s), thus the 2D ZnO can serve as a promising material to fill in the gap for deep‐UV photodetection. The method developed here opens a new avenue to controllably synthesize 2D nonlayered materials and accelerates their applications in high‐performance optoelectronic devices. Abstract : A controllable and simple strategy is designed to synthesize atomic‐thin 2D nonlayered ZnO nanosheets via water‐soluble surfactant‐assisted synthesis. The solution‐processed 2D ZnO is compatible with the traditional device fabrication process and shows a wonderful visible‐blind UV photodetection performance with the highest responsivity of 2.0 × 10 4 A W −1 and detectivity of 6.93 × 10 14 Jones at the wavelength of 254 nm.